ABOUT ENLIGHTENMENT AHMAD DANISH IN THE WORKS OF SHARIFJON MAHDUM SADRI ZIYO - Dilnoza Uktamovna Yangiboeva (Scholar Express Journal, 2021)
Despite the difficult economic and political situation at the ending of XIX-the beginning of the XX centuries, the scientific and literary environment in the Emirate of Bukhara has developed. In this period, many enlighteners such as Ahmad Danish, Qori Rahmatullah Vozeh, Shamsiddin Shahin, Abdukadirhoja Savdo, Mirzo Abdulazim Somi, Hayit Sahbo, Sharifjon Sadri Ziyo had lived and worked. They sharply criticized the social evils of society, the injustices of the rulers and officials in their works. It is reflected scientific information about the unique role of the great enlightener Ahmad Danish in the scientific and cultural environment of Bukhara in the works of Muhammad Sharifjon Mahdum Sadri Ziyo in this article.
Keywords: Tazkori ash'ar; Navodiri; enlightenment circles; Navodir ul-vaqo'e